Clustered Core- and Pan-Genome Content on Rhodobacteraceae Chromosomes - Kopejtka, Karel; Lin, Yan; Jakubovičová, Markéta; Koblížek, Michal; Tomasch, Jürgen (Genome biology and evolution, 2019)
In Bacteria, chromosome replication starts at a single origin of replication and proceeds on both replichores. Due to its asymmetric nature, replication influences chromosome structure and gene organization, mutation rate, and expression. To date, little is known about the distribution of highly conserved genes over the bacterial chromosome. Here, we used a set of 101 fully sequenced Rhodobacteraceae representatives to analyze the relationship between conservation of genes within this family and their distance from the origin of replication. Twenty-two of the analyzed species had core genes clustered significantly closer to the origin of replication with representatives of the genus Celeribacter being the most apparent example. Interestingly, there were also eight species with the opposite organization. In particular, Rhodobaca barguzinensis and Loktanella vestfoldensis showed a significant increase of core genes with distance from the origin of replication. The uneven distribution of low-conserved regions is in particular pronounced for genomes in which the halves of one replichore differ in their conserved gene content. Phage integration and horizontal gene transfer partially explain the scattered nature of Rhodobacteraceae genomes. Our findings lay the foundation for a better understanding of bacterial genome evolution and the role of replication therein.
Keywords: fylogeneze; Bacterial Proteins; bakteriální chromozomy; Chromosomes, Bacterial; Genome, Bacterial; Rhodobacteraceae; Phylogeny; Gene Expression Regulation, Bacterial; genom bakteriální; regulace genové exprese u bakterií; DNA Replication; replikace DNA; bakteriální proteiny